Small Ruminant Production Based on Rangelands to Optimize Animal Nutrition and Health: Building an Interdisciplinary Approach to Evaluate Nutraceutical Plants - Rafael Arturo Torres-Fajardo; Pedro Geraldo González-Pech; Carlos Alfredo Sandoval-Castro; Juan Felipe de Jesús Torres-Acosta (Animals, 2020)
The plant kingdom can influence the productivity and health of herbivores at different levels. However, demonstrating this process in a scientific manner entails substantial endeavors from different disciplines. In the present review, we will describe the features of a native vegetation system traditionally used by small ruminants and use its particularities to build an interdisciplinary approach to evaluate the nutraceutical properties of plants. Initially, we will establish the context of the low deciduous forest (LDF), considering some botanical and nutritional aspects, as well as the presence of plant secondary compounds (PSC) and gastrointestinal nematodes (GIN). Furthermore, we will focus on coevolutionary aspects that undoubtedly shaped the plants–nutrients–PSC–GIN–herbivore relationship. In addition, the concept of nutraceutical will be discussed to provide clarity and aspects to be considered for their evaluation. Then, ethological, agronomical, nutritional, PSC, parasitological and animal species issues are deepened placing emphasis on methodological approaches. Special focus is given to condensed tannins, as they are the fourth largest group of PSCs and the most studied in livestock sciences. Validation of the nutraceutical properties of plants from native vegetation systems should be seen as a process derived from many scientific disciplines that feed into each other in a cyclic manner.